Хөдөө тосгоны хараа хÿналтгүй хүүхдүүдийн асран хамгааллын хэлбэр, давуу болон сул тал (Өвөр Монголын Өөртөө Засах Орны Тунляо хотын Баолуншань сум, Найман сум, Ганьчика сумдын жишээгээр): Mode of Care for Abandoned Children in Rural Villages, its Advantages and Weakness (On the examples of Baolongshan soum, Ganqika soum and Naiman soum of Tongliao city of the Inner Mongolian Autonomous Region) - Lijuan, Lu (Mongolian Journal of Foreign Languages and Cultures, 2023)
The 21st century is the technological and industrial era. In this sense, there are many changes in the way of life of us, the humanity and causing many problems. This problem hasn’t skipped the life of rural people in the People’s Republic of China. Homeless children is one of the important burning problems, they face. I have made research based on Baolongshan soum, Ganqika soum and Naiman soum of Tongliao city of the Inner Mongolian Autonomous Region. because there are many problems such as parents leave their children with their grandparents, siblings, friends, and neighbors to work elsewhere, parents don’t pay enough attention on their children’s education and they are not able to help their children which can lead to conflicts and misunderstandings between their children and caregivers.